Dim light, sleep tight, and wake up bright - Sleep optimization in athletes by means of light regulation - Knufinke, M.; Nieuwenhuys, A.; Geurts, S. A. E.; Møst, E. I. S.; Moen, M. H.; Maase, K.; Coenen, A. M. L.; Gordijn, M. C. M.; Kompier, M. A. J. (European Journal of Sport Science, 2021)
Despite an elevated recovery need, research indicates that athletes often exhibit relatively poor sleep. Timing and consolidation of sleep is driven by the circadian system, which requires periodic light-dark exposure for stable entrainment to the 24-hour day, but is often disturbed due to underexposure to light in the morning (e.g. low-level indoor lighting) and overexposure to light in the evening (e.g. environmental and screen-light). This study examined whether combining fixed sleep schedules with light regulation leads to more consolidated sleep. Morning light exposure was increased using light-emitting goggles, whereas evening light exposure was reduced using amber-lens glasses.